Evaluation of growth, yield attributes, and yield of wheat varieties under Terminalia chebula trees - Kumar, Akshay; Gupta, Meenakshi; Gupta, L. M.; Kour, Sarabdeep; Choudhary, Punit (Frontiers in Sustainable Food Systems, 2025)
Agroforestry can simultaneously satisfy three important objectives viz., protecting the ecosystems; producing a high level output of economic goods; and increasing income and basic needs of rural population besides maintaining the resource base. In Jammu subtropics many fruit trees are grown with grasses or as sole crop. There isn't much awareness among farmers about the benefits of agroforestry.To overcome this, we had conducted a field trial at the Experimental farm of the Division of Agroforestry, Chatha with the aim of exploring the possibility of growing different wheat varieties as an intercrop under the canopy of harad (Terminalia chebula Retz.) trees planted at a spacing of 5×4 m 2 . Three wheat varieties viz. JAUW-598, WH-1080, and RSP-561 were grown under the Terminalia chebula trees, and growth and yield parameters were recorded at two distances from the base of the tree (0-1m and 1-2m). This study investigates the impact of distance from Terminalia chebula (harad) trees on the growth and yield of different wheat varieties in the agro-climatic conditions of Jammu and Kashmir. The primary objective is to determine the optimal spacing that minimizes competition for resources between the trees and crops, thereby enhancing wheat productivity. By evaluating key growth parameters and yield at varying distances from the tree base, this research aims to provide actionable insights for optimizing intercropping systems in the region. The growth and yield of varieties were significantly reduced under shade as compared to sole cropping. Maximum spike length (13.91 cm), tillers/plant (7.36), grains/spike (33.62) and grain yield (42.46 qha -1 ) were recorded in variety RSP-561 grown in open. Overall, RSP-561 performed better among all the other varieties with a yield reduction of 47.83%, 12.15% at 0-1m and 1-2m distance, respectively, under shade as compared to the open conditions. All wheat varieties performed better at a distance of 1-2m away from the tree base as the amount of shade/competition is less compared to 0-1m distance from the tree base. The study concluded that wheat can be successfully grown at 1-2m distance from the tree base to attain an additional income from Terminalia chebula orchard.